Mermaid tales from around the world - Osborne, Mary Pope.; Howell, Troy (New York : Scholastic, 1993)
A collection of twelve mermaid tales from around the world, featuring such sources as France, Greece, and North Africa.
Includes bibliography (p.84)
Keywords: Mermaids; Tales; Mermaids; Folklore